Low-temperature zinc ion battery high-entropy eutectic electrolyte and preparation method and application thereof
Through eutectic reaction and solvent addition, a high entropy eutectic electrolyte was prepared, which solved the problems of difficulty in operating the zinc ion battery at low temperatures and the growth of zinc negative dendrites, and achieved high ionic conductivity and excellent cycle life and rate performance.
Patent Information
- Application Number
- CN202411587297.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-28
AI Technical Summary
The existing zinc-ion battery liquid electrolyte is difficult to operate at low temperatures, and zinc negative electrodes are prone to problems such as dendrite growth, corrosion and hydrogen evolution reaction, and the electrolyte operates at extremely small current density.
The freezing point is reduced by eutectic reaction, a high-entropy eutectic electrolyte is prepared, a hydrogen bond donor and a hydrogen bond acceptor are added, and a solvent is added on the basis of it to increase the entropy of the electrolyte, thereby maintaining the liquid state at -20°C and improving the ionic conductivity.
It realizes that the zinc ion battery does not freeze at -20°C and has high ionic conductivity, which inhibits the growth and hydrogen evolution problems of zinc dendrites, and improves the cycle life and rate performance of the battery.
Smart Images

Figure CN119542545A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a low-temperature zinc ion battery high-entropy eutectic electrolyte and a preparation method and application thereof. Background Art
[0002] Environmental problems are becoming increasingly prominent, and the global energy market is turbulent. Improving the energy structure and ensuring energy security have become urgent tasks. Therefore, electrochemical technology capable of large-scale energy storage has become an alternative for the next generation of energy storage and transmission. Among various rechargeable batteries, lithium-ion batteries are currently the most mature commercial secondary battery energy storage system. Because of their relatively high output voltage, high energy density and long service life, they are widely used in daily electric vehicles and electronic products markets. However, lithium-ion batteries have problems such as lack of lithium resources, high cost, low safety of active metals, toxic and flammable organic electrolytes, and complex processes, which limit the application of lithium-ion batteries. Therefore, there is an urgent need for energy storage systems that can replace lithium-ion batteries.
[0003] Among the currently commercialized rechargeable secondary batteries, zinc-ion batteries (ZIBs) have become one of the most promising energy storage systems due to their low redox potential, high theoretical capacity, abundant resources and environmental protection. In recent years, the research work on zinc-ion batteries has mainly focused on positive electrode materials, zinc negative electrodes, electrolytes and separators. As the main part of mass transfer and conduction, the electrolyte is in contact with the positive electrode material, zinc negative electrode and separator of the battery, and participates in most battery reactions, playing a particularly important role. Zinc-ion battery electrolytes can be classified into electrolytes, gel electrolytes and solid electrolytes according to their state, and electrolytes can be divided into organic electrolytes and aqueous electrolytes, each of which has its own characteristics. The electrolyte is easy to prepare, has lower cost, is easier to assemble, and has higher ion conductivity, but it is easy to evaporate at high temperatures and freeze at low temperatures; solid electrolytes have good mechanical properties and a wide applicable temperature range, but are difficult to use due to their complex preparation process, low ion conductivity, and interface problems between the electrolyte and the positive and negative electrodes; gel electrolytes are between liquid electrolytes and solid electrolytes, and have all the characteristics of both, but are not economically efficient, so they are difficult to meet practical applications.
[0004] Liquid electrolytes are widely used due to their low cost and high efficiency. Antifreeze electrolytes that can operate stably at low temperatures are even more popular. However, due to the characteristics of aqueous electrolytes themselves, it is difficult to achieve antifreeze, and aqueous antifreeze electrolytes are also a major difficulty for liquid electrolytes. The optimization design of liquid electrolytes mainly includes the following categories: electrolyte additives, eutectic electrolytes, high entropy electrolytes, organic electrolytes, ionic liquid electrolytes, and "salt-in-water" electrolytes. Among them, electrolyte additives have limited improvement on the low-temperature performance of batteries, organic electrolytes and ionic liquid electrolytes are generally more expensive, and salt-in-water electrolytes are difficult to inhibit the dendrite growth of zinc negative electrodes. Eutectic electrolytes and high entropy electrolytes have a wide range of raw materials, and substances that can inhibit dendrite growth can be selected as raw materials. They can reduce the freezing point by reducing the order in the system, and maintain their high ionic conductivity by maintaining liquid at low temperatures, which can effectively improve the performance of aqueous electrolytes at low temperatures.
[0005] Today's aqueous zinc-ion batteries face problems such as zinc negative electrode dendrite growth, zinc negative electrode corrosion, hydrogen evolution and passivation. In addition, aqueous electrolytes are prone to freezing in low-temperature environments. The advantages of eutectic electrolytes and high-entropy electrolytes can effectively solve these problems, but today's zinc-ion battery eutectic electrolytes have high viscosity due to the lack of solvents, making it difficult to show satisfactory mass transfer capabilities, while there are few studies on zinc-ion battery high-entropy electrolytes, and few have shown excellent performance at low temperatures. Therefore, it is particularly important to design a low-cost, low-temperature eutectic high-entropy electrolyte that combines the advantages of eutectic electrolytes and high-entropy electrolytes.
[0006] Patent document CN 118281313 A discloses the application of a composite gel electrolyte based on a deep eutectic solution in a zinc ion battery. The operating temperature range of the zinc ion battery is -5 to 50°C. The preparation method of the composite gel electrolyte includes the following steps: a. Stirring and mixing a hydrogen bond acceptor and a hydrogen bond donor at 40 to 100°C to obtain a transparent deep eutectic solution; the hydrogen bond acceptor is selected from one of choline chloride, zinc chloride or glycine. The hydrogen bond donor is selected from one of urea, ethylene glycol, propylene glycol, thiourea, glucose or butanediol. This patent uses hydroxyl as a hydrogen bond donor, which can only maintain a gel state at low temperatures, and its current density at low temperatures is only 0.2 mAcm -2 , the performance is average. Summary of the invention
[0007] The purpose of the present invention is to solve at least one of the following technical problems existing in the prior art: first, the problem that conventional liquid zinc ion electrolyte cannot operate at low temperature; second, the problems of zinc negative electrode dendrite growth, corrosion, hydrogen evolution reaction, etc.; third, the problem that conventional electrolytes or electrolytes can only operate at extremely low current density. Therefore, a preparation method and application of a high entropy eutectic electrolyte for a low-temperature zinc ion battery are provided, wherein the freezing point is initially lowered by a eutectic reaction, so that the solid material at room temperature is transformed and maintained in a liquid phase; and then a substance that can increase the entropy of the electrolyte is added to the above eutectic electrolyte, thereby obtaining a high entropy eutectic electrolyte.
[0008] The technical solution of the present invention is as follows:
[0009] A first aspect of the present invention provides a low-temperature zinc ion battery high entropy eutectic electrolyte, the electrolyte comprising: a hydrogen bond donor, a hydrogen bond acceptor and a solvent;
[0010] The hydrogen bond donor is at least one of methylsulfonamide, thioformamide, butyramide, asparagine, tert-butylamine, dimethylpropylenediamine, oxalyl diamide, benzamide, sulfamide and ethylsulfonamide;
[0011] The hydrogen bond acceptor is at least one of aspartic acid, glutamic acid, methionine, zinc chloride, zinc perchlorate, zinc fluoroborate and zinc acetate;
[0012] And when the hydrogen bond acceptor is at least one of aspartic acid, glutamic acid and methionine, the electrolyte further includes a zinc salt.
[0013] Optionally, the solvent is at least one of deionized water, ethylene glycol, methanol, glycerol, dimethyl sulfoxide, formamide, acetonitrile and butyronitrile.
[0014] Optionally, the amount of the solvent is 10-50%wt of the total amount of the electrolyte;
[0015] When there are two solvents, the two solvents each account for 10% to 90% by molar ratio;
[0016] When there are three kinds of solvents, calculated by molar ratio, each of the three kinds of solvents accounts for 10% to 80%.
[0017] Optionally, the zinc salt is at least one of zinc chloride, zinc perchlorate, zinc fluoborate, zinc sulfate and zinc acetate;
[0018] Optionally, the amount of the zinc salt used is 10-60%wt of the total mass of the hydrogen bond acceptor and the hydrogen bond donor.
[0019] Optionally, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 0.5:1 to 8:1.
[0020] Optionally, when there are two hydrogen bond donors, the two hydrogen bond donors each account for 10% to 90% by molar ratio; when there are three hydrogen bond donors, the three hydrogen bond donors each account for 10% to 80% by molar ratio;
[0021] When there are two hydrogen bond acceptors, calculated by molar ratio, each of the two hydrogen bond acceptors accounts for 10% to 90%; when there are three hydrogen bond acceptors, calculated by molar ratio, each of the three hydrogen bond acceptors accounts for 10% to 80%; when there are four hydrogen bond acceptors, calculated by molar ratio, each of the four hydrogen bond acceptors accounts for 10% to 70%.
[0022] A second aspect of the present invention provides a method for preparing a low-temperature zinc ion battery high entropy eutectic electrolyte, comprising the following steps:
[0023] S1. Mixing a hydrogen bond donor and a hydrogen bond acceptor, heating, and converting the solid into a liquid phase to prepare a eutectic electrolyte;
[0024] S2. Add a solvent to the eutectic electrolyte, mix well, and obtain a high entropy eutectic electrolyte.
[0025] Optionally, in step S1, the heating temperature is 80-120° C., and the heating time is 1.5-2.5 h;
[0026] In step S2, the mixing time is 0.5 to 1.5 hours.
[0027] A third aspect of the present invention provides a zinc ion battery, comprising the electrolyte described above or the electrolyte prepared by the method described above.
[0028] The present invention has at least one of the following beneficial effects:
[0029] The present invention uses -NH2 of amine or amide substances as a hydrogen bond donor and a salt with a halogen or carboxyl group as a hydrogen bond acceptor to form a hydrogen bond and generate a eutectic reaction. The prepared eutectic solution has a lower freezing point than the reactant and can remain in a liquid state at room temperature without the addition of a solvent. A solvent is added to increase the disorder of the electrolyte to prepare a high-entropy eutectic electrolyte, further reducing the freezing point of the electrolyte system, and finally preparing a high-entropy eutectic electrolyte for zinc ion batteries that does not freeze at -20°C and has high ionic conductivity. The battery assembled with this electrolyte can operate stably at -20°C, and can guide zinc to be oriented perpendicular to the zinc negative electrode, presenting an orderly, compact, and flat deposition, effectively inhibiting the wanton growth of zinc dendrites and the problem of hydrogen evolution at the zinc negative electrode, and showing excellent cycle life and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The figures are the actual pictures of the zinc ion battery eutectic electrolyte without adding solvent in Comparative Example 1 (left) and Comparative Example 2 (right) of the present invention;
[0031] Figure 2 It is a physical picture of the preparation of eutectic electrolytes of Comparative Examples 2, 3, 4 and 5 of the present invention;
[0032] Figure 3 It is a physical picture of the eutectic electrolyte of Comparative Examples 2, 3, 4, and 5 of the present invention at -20°C;
[0033] Figure 4 The actual pictures of the high entropy eutectic electrolytes of Example 1 (left) and Example 9 (right) of the present invention at -20°C
[0034] Figure 5 This is a physical picture of the high entropy eutectic electrolyte of Comparative Example 9 of the present invention at -20°C;
[0035] Figure 6 is an infrared spectrum of a low-temperature zinc ion battery high entropy eutectic electrolyte obtained in Example 1 of the present invention;
[0036] Figure 7 This is the rate performance curve of a Zn||Zn battery assembled with a high entropy eutectic electrolyte for a low-temperature zinc ion battery obtained in Example 1 of the present invention at 30°C;
[0037] Figure 8 The cyclic stability curve of the Zn||Zn battery assembled with the high entropy eutectic electrolyte of the low-temperature zinc ion battery obtained in Example 1 of the present invention at 30°C, with a current density of 1 mA / cm 2 , with a surface capacity of 1 mAh / cm 2 ;
[0038] Fig. 9 The cyclic stability curve of the Zn||Zn battery assembled with the high entropy eutectic electrolyte of the low-temperature zinc ion battery obtained in Example 1 of the present invention at -20°C, with a current density of 1 mA / cm 2 , with a surface capacity of 1 mAh / cm 2 ;
[0039] Fig.10 This is the cycle stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||MnO2 battery at 30°C obtained in Example 1 of the present invention;
[0040] Fig.11 This is the charge and discharge curve of the Zn||MnO2 battery assembled with the high entropy eutectic electrolyte of the low-temperature zinc ion battery obtained in Example 1 of the present invention at 30°C;
[0041] Fig.12This is the cycle stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||MnO2 battery at -20°C obtained in Example 1 of the present invention;
[0042] Fig.13 This is the charge and discharge curve of the Zn||MnO2 battery assembled with the high entropy eutectic electrolyte of the low-temperature zinc ion battery obtained in Example 1 of the present invention at -20°C;
[0043] Fig.14 This is a SEM image of a zinc negative electrode deposited using a high entropy eutectic electrolyte for a low-temperature zinc ion battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0044] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] An embodiment of the present invention provides a high entropy eutectic electrolyte for a low-temperature zinc ion battery, the electrolyte comprising: a hydrogen bond donor, a hydrogen bond acceptor and a solvent;
[0046] The hydrogen bond donor is at least one of methylsulfonamide, thioformamide, butyramide, asparagine, tert-butylamine, dimethylpropylenediamine, oxalyl diamide, benzamide, sulfamide and ethylsulfonamide;
[0047] The hydrogen bond acceptor is at least one of aspartic acid, glutamic acid, methionine, zinc chloride, zinc perchlorate, zinc fluoroborate and zinc acetate;
[0048] And when the hydrogen bond acceptor is at least one of aspartic acid, glutamic acid and methionine, the electrolyte further includes a zinc salt.
[0049] The hydrogen bond donor of the present invention contains -NH2, and the hydrogen bond acceptor contains halogen or carboxyl. -NH2 and halogen or carboxyl can form hydrogen bonds and undergo eutectic reactions. The prepared eutectic solution has a lower freezing point than the reactants. The chaos of the electrolyte is increased by adding a solvent, because the change from liquid phase to solid phase is an entropy reduction process with reduced chaos. Therefore, the electrolyte has a higher entropy, which can make the solidification process more difficult, thereby further reducing the freezing point. The freezing point is reduced by the above two steps to achieve the effect of not solidifying at low temperatures. The present invention prepares a high entropy eutectic electrolyte, further reduces the freezing point of the electrolyte system, and finally prepares a high entropy eutectic electrolyte for zinc ion batteries that does not freeze at -20°C and has high ionic conductivity.
[0050] In some embodiments, the solvent is at least one of deionized water, ethylene glycol, methanol, glycerol, dimethyl sulfoxide, formamide, acetonitrile and butyronitrile.
[0051] In some embodiments, the amount of the solvent used is 10-50%wt of the total amount of the electrolyte; preferably 20-50%wt, more preferably 30-40%; specifically 10%wt, 15%wt, 20%wt, 25%wt, 30%wt, 35%wt or 40%wt, etc.
[0052] When there are two solvents, the two solvents each account for 10% to 90% by molar ratio;
[0053] When there are three kinds of solvents, calculated by molar ratio, each of the three kinds of solvents accounts for 10% to 80%.
[0054] In some embodiments, the zinc salt is at least one of zinc chloride, zinc perchlorate, zinc fluoroborate, zinc sulfate, and zinc acetate.
[0055] In some embodiments, the amount of the zinc salt is 10-60%wt of the sum of the mass of the hydrogen bond acceptor and the hydrogen bond donor, preferably 25-55%wt, more preferably 30-40%; specifically, it can be 10%wt, 15%wt, 20%wt, 25%wt, 30%wt, 35%wt or 40%wt, etc.
[0056] Optionally, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 0.5-8:1, preferably 1-7:1, more preferably 2-6:1; specifically, it can be 0.8:1, 1:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, 7:1, etc.
[0057] Optionally, when there are two hydrogen bond donors, the two hydrogen bond donors each account for 10% to 90% by molar ratio; when there are three hydrogen bond donors, the three hydrogen bond donors each account for 10% to 80% by molar ratio;
[0058] When there are two hydrogen bond acceptors, calculated by molar ratio, each of the two hydrogen bond acceptors accounts for 10% to 90%; when there are three hydrogen bond acceptors, calculated by molar ratio, each of the three hydrogen bond acceptors accounts for 10% to 80%; when there are four hydrogen bond acceptors, calculated by molar ratio, each of the four hydrogen bond acceptors accounts for 10% to 70%.
[0059] A second aspect of the present invention provides a method for preparing a low-temperature zinc ion battery high entropy eutectic electrolyte, comprising the following steps:
[0060] S1. Mixing a hydrogen bond donor and a hydrogen bond acceptor, heating, and converting the solid into a liquid phase to prepare a eutectic electrolyte;
[0061] S2. Add a solvent to the eutectic electrolyte, mix well, and obtain a high entropy eutectic electrolyte.
[0062] By forming hydrogen bonds between amino groups and halogen or carboxyl groups, a eutectic reaction occurs to reduce order, and a eutectic electrolyte is prepared by heating and stirring. A solvent is then added to increase the entropy of the electrolyte to prepare a high-entropy eutectic electrolyte for a low-temperature zinc ion battery.
[0063] In some embodiments, the technical scheme used by the present invention to achieve the above-mentioned objectives is as follows: (1) using one or more amines or amides such as methylsulfonamide (MSA), thioformamide (TMA), butyramide (n-BA), asparagine, thiourea (TU), tert-butylamine (TBA), dimethylpropylenediamine (DPA), oxalyl diamide (OA), benzamide (BA), sulfamide (SA), ethylsulfonamide (ESA) as hydrogen bond donors, and using one or more of aspartic acid (L-AA), glutamic acid (L-GA), methionine (DL-M), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc fluoroborate (Zn(BF4)2), and zinc acetate (ZnAc2) as hydrogen bond acceptors, and heating and stirring to cause a eutectic reaction to initially lower the freezing point, so that the solid material at room temperature is transformed and maintained in a liquid phase. When there is no zinc salt in the hydrogen bond acceptor, zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc fluoroborate (Zn(BF4)2), zinc sulfate (ZnSO4), and zinc acetate (ZnAc2) are used as zinc salts. The hydrogen bond donor and the hydrogen bond acceptor are first mixed, and a eutectic reaction occurs under heating and stirring, and the mixture is transformed into a liquid phase to become a eutectic solution. Then, the zinc salt is added to form a eutectic electrolyte.
[0064] (2) Add one or more of deionized water (H2O), ethylene glycol (EG), methanol (MA), glycerol (GL), dimethyl sulfoxide (DMSO), formamide (FA), acetonitrile (AT), and butyronitrile (BT) to the above eutectic electrolyte to increase the entropy of the electrolyte and obtain a high-entropy eutectic electrolyte. Because the transition from liquid to solid is an entropy reduction process with reduced disorder, the electrolyte with a higher entropy can make the solidification process more difficult, so the solidification point can be further reduced. By lowering the solidification point through the above two steps, the effect of not solidifying at low temperatures can be achieved.
[0065] In some embodiments, in step S1, the heating temperature is 80-120°C, and the heating time is 1.5-2.5h; preferably, the heating temperature is 90-110°C, and the heating time is 1.7-2.3h; more preferably, the heating temperature is 95-105°C, and the heating time is 1.9-2.1h; the heating temperature can specifically be 80, 90, 100, 110, 120°C, etc., and the heating time can specifically be 1.5, 2, 2.5h, etc.
[0066] In step S2, the mixing time is 0.5 to 1.5 h, preferably, the mixing time is 0.7 to 1.3 h; more preferably, the mixing time is 0.9 to 1.1 h; the mixing time can specifically be 0.5, 1, 1.5 h, etc.
[0067] A third aspect of the present invention provides a zinc ion battery, comprising the electrolyte described above or the electrolyte prepared by the method described above.
[0068] The zinc ion battery prepared by the invention has excellent cycle life and rate performance.
[0069] The advantages and highlights of the present invention are:
[0070] 1. Liquid electrolyte can be prepared without solvent. In the first step of preparing the electrolyte, through eutectic reaction, without any solvent, multiple solids can be heated and mixed to become liquid and remain liquid.
[0071] 2. Safe, non-toxic and harmless. Compared with lithium-ion batteries, potassium-ion batteries and sodium-ion batteries that need to be isolated from water and oxygen, this electrolyte is used for aqueous zinc-ion batteries, and the electrolyte can be prepared and the battery assembled in the air. At the same time, lithium-ion batteries, sodium-ion batteries and potassium-ion batteries all require toxic and volatile organic solvents, while the solvent in this work can be non-toxic and harmless water, which is safe and environmentally friendly.
[0072] 3. Maintain a liquid state with high ionic conductivity at low temperatures. Common low-temperature electrolytes are gel or solid. The electrolyte in this work is liquid at -20°C, so it can have a higher ionic conductivity and meet the requirements of 1mA / cm at low temperatures. 2 It can operate stably at 30mA / cm 2 It operates stably at a current density of 2.5 %.
[0073] 4. Guide zinc deposition behavior and extend the negative electrode life. The low-temperature high-entropy eutectic electrolyte prepared by the present invention is added with amide salts that can be preferentially adsorbed on a specific crystal face of zinc, thereby occupying the zinc deposition site of this crystal face, and then guiding zinc to be deposited on the specified crystal face to form an ordered and dense vertically oriented zinc. At the same time, the amide salts guide zinc to be preferentially adsorbed on the zinc surface, inhibit the tip effect, guide zinc to be uniformly deposited, and effectively inhibit the growth of zinc dendrites.
[0074] The high entropy eutectic electrolyte for low-temperature aqueous zinc ion batteries prepared by the present invention can remain liquid without freezing at -20°C, and the battery can be charged at 1 mA / cm 2At the same time, this electrolyte successfully guided the deposited zinc to grow in a tightly ordered orientation perpendicular to the zinc negative electrode, greatly regulating the growth of zinc dendrites. Due to its high ionic conductivity and ability to guide zinc growth orientation, the assembled battery can operate at 30 mA / cm 2 It can operate stably at a current density of , which significantly improves the rate performance of zinc-ion batteries.
[0075] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0076] The raw materials include: methylsulfonamide (MSA), thioformamide (TMA), butyramide (n-BA), asparagine, thiourea (TU), tert-butylamine (TBA), dimethylpropylenediamine (DPA), oxalyldiamide (OA), benzamide (BA), sulfamide (SA), ethylsulfonamide (ESA), aspartic acid (L-AA), glutamic acid (L-GA), methionine (DL-M), zinc chloride (ZnCl2), zinc perchlorate (Zn(ClO4)2), zinc fluoroborate (Zn(BF4)2), zinc acetate (ZnAc2), deionized water (H2O), ethylene glycol (EG), methanol (MA), glycerol (GL), dimethyl sulfoxide (DMSO), formamide (FA), acetonitrile (AT), butyronitrile (BT). The raw materials are all commercially available.
[0077] Example 1
[0078] This example prepares a low-temperature zinc ion battery high entropy eutectic electrolyte, and the specific preparation steps are as follows:
[0079] 1) Prepare eutectic electrolyte: weigh MSA:ZnCl2 with a molar ratio of 1:1, i.e. 0.95 g MSA and 1.36 g ZnCl2, stir and mix, heat to 100°C and keep for 2 hours to obtain a eutectic electrolyte.
[0080] 2) Prepare high entropy eutectic electrolyte: Add 0.42 ml of H2O to the above eutectic electrolyte and stir at room temperature for 1 hour to obtain a high entropy eutectic electrolyte.
[0081] 3) Zn||Zn battery performance test: The prepared high entropy eutectic electrolyte was used as the electrolyte for zinc ion battery assembly. The pole pieces used in the Zn||Zn battery were all zinc discs with a thickness of 100μm and a diameter of 10mm. The diaphragm was a type A glass fiber diaphragm with a diameter of 16mm. They were assembled into 2025 button-type Zn||Zn symmetrical batteries. The performance test was mainly carried out using the Xinwei battery test system at 1mA / cm 2 Current density and 1mAh / cm 2The cycle performance test was carried out at the surface capacity, and the rate performance current density range was 0.5~30mA / cm 2 .
[0082] 4) Zn||MnO2 battery performance test: The prepared high entropy eutectic electrolyte was used as the zinc ion battery electrolyte for battery assembly. The negative electrode used in the Zn||MnO2 battery was a zinc disc with a thickness of 100μm and a diameter of 10mm, and the positive electrode was a MnO2 pole piece with a diameter of 12mm. The active material loading of the MnO2 pole piece was between 0.5 and 2mg. The current collector was Ti foil, and the diaphragm was a type A glass fiber diaphragm with a diameter of 16mm. It was assembled into a 2025 button-type Zn||Zn symmetrical battery. The performance test was mainly carried out using the Xinwei battery test system, and the charge and discharge performance test was carried out at a current density of 0.5A / g.
[0083] The actual picture of the high entropy eutectic electrolyte prepared in Example 1 at -20°C is as follows Figure 4 As shown in the left figure, it can be maintained in a liquid state.
[0084] Figure 6 is the infrared spectrum of the low-temperature zinc ion battery high entropy eutectic electrolyte obtained in Example 1, Figure 6 This indicates the successful preparation of the high entropy eutectic electrolyte in Example 1.
[0085] Figure 7 is the rate performance curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||Zn battery at 30°C obtained in Example 1, Figure 7 It can be seen that the electrolyte of Example 1 can be used at 30 mA / cm 2 It operates stably at a current density of 2.5 %.
[0086] Figure 8 The cyclic stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||Zn battery obtained in Example 1 at 30°C, with a current density of 1 mA / cm 2 , with a surface capacity of 1 mAh / cm 2 ;Depend on Figure 8 It can be seen that the electrolyte of Example 1 can be stably circulated for more than 1600 hours, far exceeding the commonly used zinc ion electrolyte.
[0087] Fig. 9 The cyclic stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||Zn battery obtained in Example 1 at -20°C, with a current density of 1 mA / cm 2 , with a surface capacity of 1 mAh / cm 2 ;Depend on Fig. 9 It can be seen that the electrolyte of Example 1 can operate stably at low temperature for more than 300 hours.
[0088] Fig.10 is the cycle stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||MnO2 battery at 30°C obtained in Example 1; Fig.10 It can be seen that the electrolyte of Example 1 can allow the Zn||MnO2 battery to be stably cycled for more than 500 times, and has a capacity retention rate of more than 85% after 500 cycles.
[0089] Fig.11 is the charge and discharge curve of the Zn||MnO2 battery assembled with the high entropy eutectic electrolyte of the low-temperature zinc ion battery obtained in Example 1 at 30°C; Fig.11 It can be seen that the Zn||MnO2 battery can be charged and discharged normally under the electrolyte of Example 1.
[0090] Fig.12 is the cycle stability curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||MnO2 battery at -20°C obtained in Example 1; Fig.12 It can be seen that the electrolyte of Example 1 can allow the Zn||MnO2 battery to stably cycle for more than 250 times at -20°C, and the capacity has not yet decayed.
[0091] Fig.13 is the charge and discharge curve of the low-temperature zinc ion battery high entropy eutectic electrolyte assembled Zn||MnO2 battery at -20°C obtained in Example 1, Fig.13 It can be seen that the Zn||MnO2 battery using the electrolyte of Example 1 can be charged and discharged normally at -20°C.
[0092] Fig.14 is a SEM image of a zinc negative electrode deposited by a high entropy eutectic electrolyte for a low-temperature zinc ion battery obtained in Example 1. Fig.14 It can be seen that the zinc deposited on the zinc negative electrode grows along the (100) crystal plane orientation, and there is no obvious dendrite protrusion, which can effectively extend the battery life.
[0093] The adsorption energy of MSA on each zinc crystal surface in the low-temperature zinc ion battery high entropy eutectic electrolyte of Example 1 is shown in Table 1:
[0094] Table 1
[0095] Unit: eV 002 side 100 faces 101 faces MSA -53.7740 -53.7740 -53.7740 * -132.8730 -152.5994 -148.4324 *MSA -186.5367 -206.7600 -204.2161 ads(adsorption energy) 0.1104 -0.3866 -2.0096
[0096] Table 1 shows that the adsorption energy of MSA with amide groups on the (101) crystal plane is lower, proving that MSA will preferentially adsorb on the (101) crystal plane, thereby occupying the growth of Zn on the (101) crystal plane and guiding the growth of Zn on the (100) crystal plane, thus obtaining Fig.14 (100) oriented growth Zn in the SEM image.
[0097] Example 2
[0098] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that the amount of ZnCl2 is fixed at 1.36 g, MSA is replaced by ESA, and ESA and ZnCl2 are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps remain unchanged.
[0099] Example 3
[0100] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that the amount of ZnCl2 is fixed at 1.36 g, MSA is replaced by SA, and SA and ZnCl2 are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps remain unchanged.
[0101] Example 4
[0102] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that the amount of ZnCl2 is fixed at 1.36 g, MSA is replaced with TMA, TMA and ZnCl2 are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps remain unchanged.
[0103] Example 5
[0104] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that ZnCl2 is replaced by Zn(ClO4)2, the amount of MSA is fixed at 0.95 g, Zn(ClO4)2 and MSA are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps remain unchanged.
[0105] Example 6
[0106] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that ZnCl2 is replaced with Zn(BF4)2 at the same time, the amount of MSA is fixed at 0.95 g, Zn(BF4)2 and MSA are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps remain unchanged.
[0107] Example 7
[0108] In this embodiment, a high entropy eutectic electrolyte is prepared, which differs from Example 1 in that ZnCl2 is replaced with L-AA at the same time, the amount of MSA is fixed at 0.95 g, L-AA and MSA are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and after heating and dissolving, ZnCl2 with the same molar mass as MSA, i.e. 1.36 g ZnCl2, is added, and other steps remain unchanged.
[0109] Example 8
[0110] In this embodiment, a eutectic electrolyte is prepared, which differs from Example 1 in that ZnCl2 is replaced with L-GA, the amount of MSA is fixed at 0.95 g, L-GA and MSA are mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and after heating and dissolving, ZnCl2 with the same molar mass as MSA, i.e. 1.36 g ZnCl2, is added, and other steps remain unchanged.
[0111] Example 9
[0112] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA, and other steps remain unchanged.
[0113] The actual picture of the high entropy eutectic electrolyte prepared in Example 9 at -20°C is as follows Figure 4 As shown in the right figure, it can be maintained in a liquid state.
[0114] Example 10
[0115] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by EG, and other steps remain unchanged.
[0116] Embodiment 11
[0117] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by DMSO, and other steps remain unchanged.
[0118] Example 12
[0119] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by GL, and other steps remain unchanged.
[0120] Example 13
[0121] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA+H2O, the volume ratio of MA:H2O is 5:5, and other steps remain unchanged.
[0122] Embodiment 14
[0123] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA+H2O, the volume ratio of MA:H2O is 4:6, and other steps remain unchanged.
[0124] Embodiment 15
[0125] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA+H2O, the volume ratio of MA:H2O is 3:7, and other steps remain unchanged.
[0126] Example 16
[0127] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA+H2O, the volume ratio of MA:H2O is 2:8, and other steps remain unchanged.
[0128] Embodiment 17
[0129] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by MA+H2O, the volume ratio of MA:H2O is 1:9, and other steps remain unchanged.
[0130] Embodiment 18
[0131] This embodiment prepares a high entropy eutectic electrolyte, which differs from Example 1 in that H2O is replaced by EG+H2O, the volume ratio of EG:H2O is 5:5, and other steps remain unchanged.
[0132] Embodiment 19
[0133] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by GL+H2O, the volume ratio of GL:H2O is 5:5, and other steps remain unchanged.
[0134] Embodiment 20
[0135] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by DMSO+H2O, the volume ratio of DMSO:H2O is 5:5, and other steps remain unchanged.
[0136] Embodiment 21
[0137] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by FA+H2O, the volume ratio of FA:H2O is 5:5, and other steps remain unchanged.
[0138] Embodiment 22
[0139] This embodiment prepares a high entropy eutectic electrolyte, which differs from Embodiment 1 in that H2O is replaced by FA+H2O+DMSA, the volume ratio of FA:H2O:DMSA is 5:3:2, and other steps remain unchanged.
[0140] Embodiment 23
[0141] This embodiment prepares a high entropy eutectic electrolyte, which differs from Example 1 in that H2O is replaced by EG+H2O+DMSA, the volume ratio of EG:H2O:DMSO is 5:3:2, and other steps remain unchanged.
[0142] Comparative Example 1
[0143] The difference between this embodiment and Example 1 is that no solvent H2O is added, and only MSA and ZnCl2 are mixed, heated and stirred at a molar ratio of 0.7:1, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte cannot be obtained under this ratio. The actual picture is as follows Figure 1 As shown in the left picture.
[0144] Comparative Example 2
[0145] The difference between this embodiment and Example 1 is that no solvent H2O is added, and only MSA and ZnCl2 are mixed, heated and stirred at a molar ratio of 10:1, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte cannot be obtained under this ratio. The actual picture is as follows Figure 1 As shown in the picture on the right.
[0146] Comparative Example 3
[0147] The difference between this embodiment and Example 1 is that: no solvent H2O is added, and MSA and ZnCl2 are only mixed, heated and stirred in a molar ratio of 1:1 to form a eutectic electrolyte, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte can be obtained under this ratio, as shown in the actual picture. Figure 2 However, the electrolyte will freeze at -20℃. Figure 3 shown.
[0148] Comparative Example 4
[0149] The difference between this embodiment and Example 1 is that no solvent H2O is added, and MSA and ZnCl2 are only mixed, heated and stirred at a molar ratio of 1.2:1, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte can be obtained under this ratio, as shown in the actual picture. Figure 2 However, the electrolyte will freeze at -20℃ and cannot remain in liquid state. Figure 3 shown.
[0150] Comparative Example 5
[0151] The difference between this embodiment and Example 1 is that no solvent H2O is added, and MSA and ZnCl2 are only mixed, heated and stirred at a molar ratio of 1.5:1, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte can be obtained under this ratio, as shown in the actual picture. Figure 3 However, the electrolyte will freeze at -20℃ and cannot remain in liquid state. Figure 3 shown.
[0152] Comparative Example 6
[0153] The difference between this embodiment and Example 1 is that no solvent H2O is added, and MSA and ZnCl2 are only mixed, heated and stirred at a molar ratio of 1.6:1, and other steps are not changed. It is found that a liquid transparent eutectic electrolyte can be obtained under this ratio, as shown in the actual picture. Figure 3 However, under this ratio, a liquid transparent eutectic electrolyte cannot be obtained and cannot be maintained in a liquid state. The actual picture is as follows Figure 3 shown.
[0154] Comparative Example 7
[0155] The difference from Example 1 is that no solvent H2O is added, and only MSA and ZnCl2 are mixed, heated and stirred in a molar ratio of 4:1, and other steps are unchanged. It is observed that the electrolyte will be frozen at -20°C.
[0156] Comparative Example 8
[0157] The difference between this and Example 1 is that the solvent H2O is not added, and only MSA and ZnCl2 are stirred and mixed, and stirred at room temperature for 2 hours. The other steps are unchanged. It is observed that the solid powder cannot be turned into liquid without heating.
[0158] Comparative Example 9
[0159] The difference between this and Example 1 is that MSA and ZnCl2 are stirred and mixed, and the temperature is raised to 60°C and maintained for 2 hours, and other steps are unchanged. It is observed that the solid cannot be turned into a liquid.
[0160] Comparative Example 10
[0161] The difference between this embodiment and Example 1 is that the amount of H2O added is changed to 1 ml, that is, the solvent accounts for more than 30 wt %. The other steps are not changed. It is observed that only a part of the liquid is maintained at -20 ° C. Figure 5 As shown, it is proved that when H2O exceeds 30wt%, the high entropy disorder level cannot be maintained and the liquid state cannot be maintained.
[0162] Comparative Example 11
[0163] The difference between this and Example 1 is that the amount of H2O added is changed to 0.2 ml, and other steps are not changed. It is observed that the liquid state cannot be maintained at -20°C.
[0164] The long cycle stability of the Zn||Zn symmetric battery prepared by the electrolyte in Examples 1 to 23 was measured, and the results are shown in Table 2:
[0165] Table 2
[0166]
[0167] It can be seen from Table 2 that the Zn||Zn symmetric batteries prepared by the electrolytes in Examples 1 to 23 have good cycle life at room temperature and at -20°C, showing excellent cycle stability, indicating that the electrolytes prepared in Examples 1 to 23 can operate stably at -20°C.
[0168] By comparing Examples 1 to 23 with Comparative Examples 1 to 11, it can be seen that the Zn||Zn symmetric battery prepared by the electrolyte in Examples 1 to 23 can maintain a liquid state and stably circulate at room temperature and at -20°C, which is significantly better than Comparative Examples 1 to 11, indicating that the ratio between the hydrogen bond donor and the hydrogen bond acceptor, whether a solvent is introduced to change the entropy, and the proportion of the introduced solvent will affect the performance of the electrolyte and its state at low temperature, thereby affecting the cycle life of the battery.
[0169] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A low-temperature zinc ion battery high entropy eutectic electrolyte, characterized in that: The electrolyte comprises: a hydrogen bond donor, a hydrogen bond acceptor and a solvent; The hydrogen bond donor is at least one of methylsulfonamide, thioformamide, butyramide, asparagine, tert-butylamine, dimethylpropylenediamine, oxalyl diamide, benzamide, sulfamide and ethylsulfonamide; The hydrogen bond acceptor is at least one of aspartic acid, glutamic acid, methionine, zinc chloride, zinc perchlorate, zinc fluoroborate and zinc acetate; And when the hydrogen bond acceptor is at least one of aspartic acid, glutamic acid and methionine, the electrolyte further includes a zinc salt.
2. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 1, characterized in that The solvent is at least one of deionized water, ethylene glycol, methanol, glycerol, dimethyl sulfoxide, formamide, acetonitrile and butyronitrile.
3. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 2, characterized in that The amount of the solvent is 10-50%wt of the total amount of the electrolyte; When there are two solvents, the two solvents each account for 10% to 90% by molar ratio; When there are three kinds of solvents, calculated by molar ratio, each of the three kinds of solvents accounts for 10% to 80%.
4. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 1, characterized in that The zinc salt is at least one of zinc chloride, zinc perchlorate, zinc fluoroborate, zinc sulfate and zinc acetate.
5. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 4, characterized in that The amount of the zinc salt used is 10-60%wt of the total mass of the hydrogen bond acceptor and the hydrogen bond donor.
6. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 1, characterized in that: The molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 0.5:1 to 8:
1.
7. The low-temperature zinc ion battery high entropy eutectic electrolyte according to claim 1, characterized in that When there are two hydrogen bond donors, the two hydrogen bond donors each account for 10% to 90% by molar ratio; when there are three hydrogen bond donors, the three hydrogen bond donors each account for 10% to 80% by molar ratio; When there are two hydrogen bond acceptors, calculated by molar ratio, each of the two hydrogen bond acceptors accounts for 10% to 90%; when there are three hydrogen bond acceptors, calculated by molar ratio, each of the three hydrogen bond acceptors accounts for 10% to 80%; when there are four hydrogen bond acceptors, calculated by molar ratio, each of the four hydrogen bond acceptors accounts for 10% to 70%.
8. A method for preparing a low-temperature zinc ion battery high entropy eutectic electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Mixing a hydrogen bond donor and a hydrogen bond acceptor, heating, and converting the solid into a liquid phase to prepare a eutectic electrolyte; S2. Add a solvent to the eutectic electrolyte, mix well, and obtain a high entropy eutectic electrolyte.
9. The preparation method according to claim 8, characterized in that: In step S1, the heating temperature is 80-120° C., and the heating time is 1.5-2.5 h; In step S2, the mixing time is 0.5 to 1.5 hours.
10. A zinc ion battery, characterized in that: The invention comprises the electrolyte according to any one of claims 1 to 7 or the electrolyte prepared by the method according to any one of claims 8 to 9.
Citation Information
Patent Citations
Application of composite gel electrolyte based on deep eutectic solution in zinc ion battery
CN118281313A
Cited By
High-temperature-resistant anhydrous eutectic electrolyte for zinc ion battery as well as preparation method and application of high-temperature-resistant anhydrous eutectic electrolyte
CN121097213A
Low-temperature electrolyte with ultrahigh water content and high reversibility
CN122068139A
Interface passivation solution based on collaborative bimolecular engineering and perovskite passivation method
CN122514176A